REFORM OF LAND ADMINISTRATION IN THE REPUBLIC OF SRPSKA - TOWARDS UNIQUE REAL ESTATE CADASTER SYSTEM - Petrović, Daliborka; Gligorić, Tihomir; Gnjatović, Dragana (Economics of Agriculture, 2013)
Topic of this article is the just started reform of land administration in the Republic of Srpska. The reform refers to the implementation of the unique Real Estate Cadaster (land and buildings registration), leaving behind the former land books system. The objective of this paper is to indicate the major reason for the reform of land administration and especially the reasons for the choice of cadastral instead of land books system. For this purpose, the historical, institutional and legal aspects are analysed and highlighted. Apart from that, public opinion is also taken into consideration by presenting the results of the short empirical survey. According to the results of the survey, the citizens of the Republic of Srpska regard the cadastral data as by far more accurate and reliable in comparison with the data from land books. Besides, European Union standards in the fled of land administration are also taken into account, because EU recommends the member states to implement the unique Real Estate Cadaster system. Based on these considerations, the choice of the unique Real Estate Cadater system instead of land books system in the Republic of Srpska represents the reasonable and justifiable step toward the reform of land administration.